Green Messaging in Indonesia’s Beauty Industry: Social Media Campaign Strategies from Garnier and Lyfe with Less - Dian Ayuria Sarwono; Aurelia Nadine Mulia (Informasi, 2026)
The awareness of sustainable beauty has increased in Indonesia, with local and global beauty companies’ entities incorporating eco-friendly campaigns into their social media strategies. The objective of this research is to identify what, why, and how beauty brands and sustainable communities implement these campaigns to engage consumers. Utilizing an in-depth qualitative approach, purposive sampling was used to conduct interviews with three key decision-makers from Garnier Indonesia and the Lyfe with Less community. The findings reveal four primary social media content communication strategies utilized to promote green beauty: transforming brand commitment, shifting towards greener products, educating consumers about sustainable living, and presenting transparent reporting to the public. By comparing a commercial mass-market brand with a grassroots minimalist community, this study contributes valuable insights into effective brand positioning, sustainability communication, and strategies for avoiding greenwashing within the Indonesian beauty industry.